Why Do Students Attend STEM Clubs, What Do They Get Out of It, and Where Are They Heading? - Margaret R. Blanchard; Kristie S. Gutierrez; Kylie J. Swanson; Karen M. Collier (MDPI AG, 2023)
This research investigated what motivated and sustained the involvement of 376 students in culturally relevant, afterschool STEM clubs at four rural, under-resourced schools. A longitudinal, convergent parallel mixed methods research design was used to investigate participants' participation in and perceptions of the clubs, their motivations to attend, and their future goals, over three years. Situated Expectancy-Value Theory (SEVT) served as a guiding theoretical and analytical framework. Overall, students who attended the clubs were African American (55%), female (56%), and 6th graders (42%), attended approximately half of the clubs (43%), and agreed with quality measures on the STEM Club Survey (M = 4.0/5). Students interviewed (n = 131) were most likely (99%) to describe what they enjoyed (intrinsic value), what was useful to them (utility value; 55%), personally important (42%; attainment value), or related to their personal or collective identity (40%). Most participants (78%) planned to attend a 4-year university and expressed interest in at least one STEM career (77%); highest attendees (48%) expressed the most interest. Our study reveals that a culturally relevant, afterschool STEM club can motivate underserved students to participate, learn, feel a sense of belonging as a club member, and positively influence their college and career pathways.